К характеристике быка домашнего (Bos taurus dometsicus L.) из древнерусского города Воиня - Тимченко, Н.Г. (Вестник зоологии, 1969)
The article is devoted to the description of the Bos taurus domesticus from the old Russian city of Voin (XI—XII) centuries that was situated in the forest-steppe zone of the present-day Ukraine. Altogether 29.5 thousands of bones were determined during excavations. These bones belonged to 500 individuals at the minimum. Adult animals amounted to 4/5 of Bos taurus domesticus population. The height in withers of Bos taurus domesticus from Voin was equal to 114.45 ±0.97 cm at an average. The individuals of 110—125 cm height in withers were the bulk of the population. Bos taurus domesticus from Voin was similar to Zolotaya Orda steppe Bos taurus domesticus and was much bigger than forest old Russian Bos taurus domesticus.